Predicting financial distress in Indonesia property sector company - Edi, Edi; Eilyn, Eilyn (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Research bankruptcy predictions and financial distress is a topic that is always researched every year because it is important for the company, investors, creditors, etc. to find out whether the company is in a healthy condition in its finances and management. This study examines the impact of financial ratios and market ratios on a company’s financial distress. These research objectives are property sector companies listed on Indonesia Stock Exchange from 2016 to 2019.  The data analysis are using the e-views program to conduct descriptive statistical tests, outlier tests, and hypothesis tests. The results show that the liquidity ratio does not have a significant effect on financial distress, while the other three financial ratios such as productivity ratios, profitability ratios, and solvency ratios have a positive effect on financial difficulties. Market ratios such as the market value of equity and leverage do not have a significant effect on the level of financial difficulty. This research is also expected to help the company to find out its financial condition so that it can immediately overcome financial problems before bankruptcy occurs.